Kolaborasi Transplantasi Karang sebagai Upaya Pelestarian Ekosistem Terumbu Karang di Pulau Samalona Kota Makassar - Nursanti, Nursanti; Nur Islah Sugianto; Wilda Oktaviani; Besse Firma Jamal; Mudasir Zainduddin (Journal of Community Service and Engagement, 2026)
Coral reef degradation on Samalona Island, Makassar City, has occurred as a result of anthropogenic pressures and changes in the marine environment. This condition directly affects the decline of ecological functions and the carrying capacity of marine ecosystems. This community service activity aims to rehabilitate coral reefs through a coral transplantation method based on collaboration between higher education institutions and the diving community. The methods employed include site surveys, fragmentation of healthy corals, attachment of coral fragments to artificial substrate media, as well as arrangement and tagging for monitoring purposes. The activity was conducted on November 25, 2025, in the waters of Samalona Island, involving lecturers from the Fisheries Science Study Program of Wira Bhakti University and partners from GGI SCUBA. The results show the successful installation of coral transplantation structures with hundreds of live coral fragments that have the potential to form new habitats for marine biota. This program is expected to gradually increase live coral cover and support the sustainability of marine ecosystems and marine tourism. This activity represents the implementation of the Tridharma of Higher Education in supporting coastal environmental conservation.